Isolation and analysis of the fission yeast gene encoding polymerase delta accessory protein PCNA. - Waseem, N H (1992)
Five monoclonal antibodies raised against rat PCNA cross-reacted with a similar protein in the fission yeast Schizosaccharomyces pombe. One of these was used to screen an S.pombe cDNA expression library. An incomplete cDNA was isolated and used to screen a genomic library, identifying a single gene, designated pcn1+ (proliferating cell nuclear antigen). The gene encodes a protein of 260 amino acids, with a deduced sequence 52% identical to human and rat PCNAs, which are 98.5% identical to each other. The budding yeast PCNA homologue POL30 is only 35% identical to the human and rat proteins. Pcn1 has a region near the C-terminus of particularly high homology to higher eukaryotic PCNA proteins. pcn1+ is essential for viability and delta pcn1 cells undergo aberrant DNA replication before cell cycle arrest. Overproduction of the protein leads to cell cycle delay in G2. Disruption of pcn1+ is complemented by the human PCNA gene, demonstrating that these genes are functional homologues.